Antioxidant and Antibacterial Properties of Methanol Extract of Gletang Flower (Tridax procumbens) - Boima Situmeang; Weny JA Musa; Nurhayati Bialangi; Sriwijayanti Sriwijayanti; Holisha Widiyanto; Dian Susvira (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
In a previous study, the methanol extract of Tridax procumbens flowers (commonly known as gletang) at high concentrations was reported to exhibit strong antibacterial activity against Streptococcus mutans and Enterococcus faecalis. This study aimed to examine the secondary metabolite content, antioxidant activity, and antibacterial activity of the methanol extract of gletang flowers. The antioxidant activity was evaluated using two methods, namely DPPH and ABTS assays. The antibacterial activity was assessed using the Kirby-Bauer method at concentrations of 1000, 5000, and 10000 ppm against Staphylococcus aureus, Escherichia coli, Streptococcus mutans, and Enterococcus faecalis. Phytochemical screening revealed that the methanol extract of gletang flowers contains phenolic compounds, flavonoids, alkaloids, and triterpenoids. The antioxidant activity tests showed very strong activity in both DPPH and ABTS assays, with IC50 values of 6.8478 ± 1.335 and 12.8608 ± 0.579 ppm, respectively. The antibacterial activity tests showed that the methanol extract of gletang flowers exhibited strong activity against E. faecalis at concentrations of 5000 and 10000 ppm, with inhibition zone diameters of 3.00 ± 0.14 and 3.20 ± 0.14 mm, respectively.